The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1978
DOI: 10.1128/aac.14.6.856
|View full text |Cite
|
Sign up to set email alerts
|

Cation Transport Alteration Associated with Plasmid-Determined Resistance to Cadmium in Staphylococcus aureus

Abstract: Plasmid-determined resistance to cadmium has only been found with plasmids from Staphylococcus aureus . Resistance to cadmium was associated with a lower accumulation of Cd 2+ ions by the plasmid-bearing resistant cells. Cadmium accumulation by susceptible cells was energy dependent and had those characteristics usually associated with a transmembrane active transport system. There was a specific interrelationship between cadmium accumulation and manganese accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
44
0
1

Year Published

1981
1981
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 30 publications
4
44
0
1
Order By: Relevance
“…Cd'+ resistance in Gram-negative bacteria such as S. aureus, Bacillus subtilis and Lactobacillus plantarum is thought to involve a plasmid-coded Cd2+ efflux system or chromosomallydetermined reduced Cd2+ uptake (Weiss et a/., 1978;Laddaga et al, 1985b;Archibald & Duong, 1984). There is no clear evidence from the studies described here that Cd'+ resistance in the Gram-negative bacterium P. putida involves a Cd'+ efflux system.…”
Section: Discussionmentioning
confidence: 99%
“…Cd'+ resistance in Gram-negative bacteria such as S. aureus, Bacillus subtilis and Lactobacillus plantarum is thought to involve a plasmid-coded Cd2+ efflux system or chromosomallydetermined reduced Cd2+ uptake (Weiss et a/., 1978;Laddaga et al, 1985b;Archibald & Duong, 1984). There is no clear evidence from the studies described here that Cd'+ resistance in the Gram-negative bacterium P. putida involves a Cd'+ efflux system.…”
Section: Discussionmentioning
confidence: 99%
“…In S. aureus, Cd2' enters the cell by the Mn2' active transport system (4,6), but cells that have the cadA gene have lower net accumulation. The CadA-efflux system is sensitive to metabolic inhibitors such as uncouplers but is not affected by agents that eliminate the membrane potential (5).…”
mentioning
confidence: 99%
“…resistance function coded by the cadA determinant results from decreased intracellular accumulation of Cd2+ (4), mediated by an energy-dependent efflux mechanism (5).…”
mentioning
confidence: 99%
“…In the present report, the induction pattern of the cadA operon by various toxic heavy metal cations is described. The cadA cadmium resistance system was previously thought to function constitutively (8,12,20,22) stop sequence, were the gifts of R. P. Novick and were used to construct cadA-blaZ fusions. Cell growth on 2XNY medium, the use of the antibiotics ampicillin (100 ,ug/ml), erythromycin (10 ,ug/ml), and chloramphenicol (5 ,ug/ml), and measurements of growth by turbidity were as described in the accompanying report (24).…”
mentioning
confidence: 99%
“…In the present report, the induction pattern of the cadA operon by various toxic heavy metal cations is described. The cadA cadmium resistance system was previously thought to function constitutively (8,12,20,22), although this hypothesis was not directly tested. As the results of our new research have shown, the inability to demonstrate regulated control of cadA was largely due to the use of Cd2' both as an inducer and as a toxic challenge compound.…”
mentioning
confidence: 99%